Occupational fatigue and sleep quality among the physicians employed in the emergency service of a COVID-19 pandemic hospital - Demir, Hüseyin Avni; Havlioğlu, Suzan (Journal of Surgery and Medicine, 2022)
Background/Aim: Outbreaks of infectious diseases, including the current COVID-19, are associated with major psychological distress and significant symptoms of mental illness. Healthcare workers may experience sleep problems, anxiety, depression, and stress when facing a major public health threat. This study aimed to assess the levels of occupational fatigue and sleep quality among the physicians working in the emergency service of a COVID-19 pandemic hospital. Methods: This descriptive study was conducted in July 2020 in Şanlıurfa Province Mehmet Akif Inan Training and Research Hospital. The sample group included 194 physicians. The Introductory Information Form prepared by the researchers, the Occupational Fatigue Exhaustion/Recovery (OFER) Scale and the Pittsburgh Sleep Quality Index (PSQI) were used for data collection. Results: The mean chronic fatigue subscale, mean acute fatigue subscale, mean recovery subscale, and mean Pittsburgh Sleep Quality Index scores were 65.30 (22.87), 69.03 (20.23), 43.93 (19.09), and 8.76 (3.20), respectively. Good and poor sleep quality levels were detected in 11.9% and 88.1% of the physicians, respectively. Sleep quality, gender, marital status, age, and anxiety status due to COVID-19 pandemic affected the occupational fatigue levels of the physicians (P<0.05). Conclusion: Assessing and minimizing the levels of occupational fatigue and implementing interventions for increasing the quality of sleep among the physicians employed in the emergency department, which has a critical place in healthcare services, are necessary.